Gagasan Modernitas dalam Pers Islam di Hindia Belanda Awal Abad XX (1915—1934) - Subuki, Makyun; Erowati, Rosida; Nurjanah, Neneng; Hudaa, Syihaabul (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
In the early 20th century, the idea of modernity emerged and continued to evolve in the press, including Islamic press. Interestingly, as part of the expression of the Muslim movement, the concept of modernity was represented distinctively. This research aims to investigate the linguistic expression in the Islamic press and link it to the concept of modernity that emerged in the early 20th century. The approach employed in this research is qualitative, with a corpus linguistic method used to collect and interpret data. The data consists of eight newspapers published between 1915 and 1934: Oetoesan Islam, Sinar Islam, Insjaf, Sawoenggaling, Al Qisthaus, Mata-Hari, Lembaga Baroe, and Pewarta Arab. Findings from this research include, firstly, 25 words expressing modernity, such as: orang, bangsa, kaoem, golongan, pergerakan, kemadjoean, perhimpoenan, kemerdikaän, studieclub, merdeka, kemerdekaan, peladjaran, pengadjaran, sekolah, sekolahan, mempeladjari, kepandaian, beladjar, soerat, kabar, toelisan, hoeroef, membatja, menoelis dan penoelis which have a significant frequency. Secondly, based on the exploration of these words, four concepts of modernity are reflected in the early 20th-century Islamic press: (1) the idea of modern education as a path to progress; (2) the concept of nationalism and awareness in organising for independence; (3) the idea of economic welfare; and (4) the importance of literacy, newspapers, and criticism of Latinization.